Preharvest Application of Gibberellic Acid and Maturity Stages on Shelf Life of Mandarin Orange - Thapa, BB; Gautam, DM (Journal of the Institute of Agriculture and Animal Science, 2002)
An experiment was carried out at Agriculture Research Center, Paripatle, Dhankuta to investigate the effect of preharvest application of GA3 and maturity stage on shelf life of mandarin. Fruits on the tree at 195 days after flowering were sprayed with 0, 15, 30 and 45 ppm of GA3. The fruits were harvested after 240, 255, 270, 285 and 300 days after flowering. The above treated fruits were stored at ambient temperature (13.5±3.5°C and 70-85% RH). During storage, there was increase in total soluble solids (TSS) and decrease in peel color development. After 60 days of storage, slightly lower level of titrable acidity (TA) and higher TSS/TA ratio was observed in GA3 treated fruits as compared to the control. GA3 treatment had significantly minimized physiological loss in weight, spoilage loss, shriveling, and thus, extended the shelf life of fruits. J. Inst. Agric. Anim. Sci. 23:41-47